ANALYSIS OF MORAL MESSAGES IN THE FILM KKN DI DESA PENARI USING ROLAND BARTHES’ SEMIOTIC ANALYSIS - Pakaya, Siti Nurhaliza; Mangge, Juliana; Putrinda; Amalia; Ntai, Sri Nuning; Wenda, Neliku (LPPM STISIPOL Mujahiddin, 2025)
This research aims to analyze the moral messages contained in the Indonesian horror film “KKN di Desa Penari” using Roland Barthes’ semiotic theory. The research method employed is qualitative analysis with a semiotic approach. The focus of the study is directed towards the denotative and connotative meanings of scenes, symbols, and visual elements within the film. The results indicate that this film conveys moral messages about the importance of respecting customs, maintaining moral boundaries, adhering to the advice of traditional figures, and enhancing spiritual awareness. The film not only provides horror entertainment but also serves as a medium for moral learning through rich symbolism and cultural myths.